2017
DOI: 10.1039/c7cc04820c
|View full text |Cite
|
Sign up to set email alerts
|

Single Ni sites distributed on N-doped carbon for selective hydrogenation of acetylene

Abstract: We prepared single Ni atoms embedded in an N-doped carbon catalyst with the assistance of metal organic frameworks. The dispersion of Ni atoms was verified by taking X-ray absorption fine structure measurements. Under the typical conditions for hydrogenation of acetylene, this single-site heterogeneous catalyst showed great potential as an alternative to Pd-based materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 37 publications
1
65
0
2
Order By: Relevance
“…Ni SAC have also been investigated on N‐doped carbon . A Ni SAC showed a conversion of acetylene and a selectivity for ethylene both over 90 %, whereas the selectivity shown by Ni nanoparticles on N‐doped carbon was less than 55 % at all tested temperatures . The excellent selectivity of the Ni SAC for ethylene may have been due to the uniform coordination of N atoms around the Ni centres, allowing to modify the electronic density on the Ni atoms.…”
Section: Catalysis With Single Atom Catalysts On Carbon‐based Materialsmentioning
confidence: 95%
“…Ni SAC have also been investigated on N‐doped carbon . A Ni SAC showed a conversion of acetylene and a selectivity for ethylene both over 90 %, whereas the selectivity shown by Ni nanoparticles on N‐doped carbon was less than 55 % at all tested temperatures . The excellent selectivity of the Ni SAC for ethylene may have been due to the uniform coordination of N atoms around the Ni centres, allowing to modify the electronic density on the Ni atoms.…”
Section: Catalysis With Single Atom Catalysts On Carbon‐based Materialsmentioning
confidence: 95%
“…Unlike Co 2+ ions, some other kinds of metal ions cannot directly form pure ZIFs with the imidazolate linker; however, they can also partly replace the zinc and gain predesigned bimetallic ZIF precursors for SACs. Through pyrolysis of NiZn ZIFs, a composite of single Ni atoms supported on N‐doped carbon (Ni SAs/NC) was successfully synthesized by Li's group, where the aggregation of Ni atoms was strictly limited by the carbon frameworks . In another example, Zhang et al exploited a chemical doping approach to fabricate Fe‐doped ZIF precursors ( Figure a) .…”
Section: Synthetic Methods Of Mof‐derived Carbon‐supported Sacsmentioning
confidence: 99%
“…Further DFT calculations revealed that H 2 preferred the N site while C 2 H 2 preferred the Pd site in the Pd‐SAC with Pd‐N 4 structure, resulting in smaller coadsorption energy of C 2 H 2 and H 2 on Pd 1 ‐N 4 and thus increasing molecular collision possibility. In another literature, nonprecious metal SACs, obtained from direct pyrolysis of bimetallic ZnNi‐ZIF, exhibited over 90% conversion of acetylene and selectivity for ethylene even at a high temperature of 200 °C, providing an effective alternative to the Pd‐based catalysts …”
Section: Applications Of Mof‐derived Carbon‐supported Sacsmentioning
confidence: 99%
“…Some references focusing on MOF-derived single-atom catalysts for other applications,s uch as organic synthesis,o r single-atom catalysts that were not derived from MOFs are also recommended to provide awider overview of the field of single-atom catalysts. [47,50,[127][128][129][130][131][132]…”
Section: Angewandte Chemiementioning
confidence: 99%